Resilience of Islamic Stock Indexes to Economic Uncertainty: Quantile-on-Quantile Insights - Ozair Siddiqui; Naveed Khan (Bank Indonesia, 2026)
This paper examines the impact of country specific EPU on Islamic stock indexes of developed, emerging, and frontier markets using Quantile on Quantile Regression (QQR). For robustness, we employ causality in mean and variance. We gather Islamic stock indexes and country specific EPU data from nine markets, classified as developed, emerging, and frontier, from January 2010 to November 2024. Our findings demonstrate that EPU exhibits predictive power for Islamic stock indexes across different quantiles (lower to higher). Additionally, the effect of EPU on respective Islamic stock indexes is asymmetric. Finally, we also show that country specific EPU negatively (positively) impacts Islamic stocks during bearish (bullish) periods of economic activity. These findings add to our understanding of and contribute to the limited literature on Islamic stock markets, highlighting their unique characteristics and responses to policy-driven uncertainties.